Le modèle cognitif et la TOE : deux points de vue sur l’identité sémantique des unités polysémiques - Olga Kravchenko-Biberson (Corela)
The present paper is concerned with the phenomenon of polysemy. Specifically, the article deals with such polysemes as verbal prefixes in Russian and verbal particles in English and discusses their semantic identity from two different theoretical perspectives : Cognitive Linguistics and Culioli’s Theory of Enunciative Operations (T.E.O). We will compare the framework of cognitive linguistics with the framework of T.E.O in order to show to which extent these two seemingly opposed theoretical approaches coincide in their efforts to come to grips with polysemy.